Frequency and Association of Distal Interphalangeal Joint Enthesitis with Nail Psoriasis in Patients with Psoriasis and Psoriatic Arthritis Presenting at a Tertiary Care Hospital in Karachi: Distal Interphalangeal Joint Enthesitis with Nail Psoriasis with Psoriasis and Psoriatic Arthritis - Ekta, .; Talat, Humaira; Mala, Pushp; Naimat, Faryal; Rais, Areeba (Pakistan Journal of Health Sciences, 2026)
Psoriasis is an autoimmune inflammatory disease that has a chronic disease or chronic illness nature, and that is commonly presented in the form of psoriatic arthritis. Objectives: To estimate the frequency and association of dip joint enthesitis with nail psoriasis in patients with psoriasis and psoriatic arthritis presenting at a tertiary care hospital in Karachi. Methods: This cross-sectional analytical study was conducted in the Department of Dermatology and Rheumatology, Civil Hospital Karachi, six months following the ethical consent. The enrolment was done through non-probability consecutive sampling among 96 patients aged 18-65 years old with or without psoriatic arthritis, having psoriasis. This data was analyzed in SPSS version 27.0, and the correlation between nail psoriasis and DIP joint enthesitis was discovered with the assistance of chi-square or Fisher’s exact test, and a p-value under 0.005 was considered to be statistically significant. Results: Nail psoriasis was found in 64.6% of the patients, and ultrasound-verified DIP joint enthesitis was observed in 37.5% of the 96 patients in this cohort. A statistically significant association was found between nail psoriasis and DIP enthesitis confirmed with ultrasound (p=0.003). Moreover, the multivariate logistic regression analysis showed that nail psoriasis was independently related to DIP joint enthesitis following the adjustment of age, sex, psoriasis duration, and occurrence of psoriatic arthritis (adjusted OR 3.52; 95% CI 1.289.67; p=0.014). Conclusion: Nail psoriasis has a strong correlation with distal interphalangeal joint enthesitis in patients with psoriasis and psoriatic arthritis.